2011
DOI: 10.1073/pnas.1106085108
|View full text |Cite
|
Sign up to set email alerts
|

Speciation with gene flow on Lord Howe Island

Abstract: Understanding the processes underlying the origin of species is a fundamental goal of biology. It is widely accepted that speciation requires an interruption of gene flow between populations: ongoing gene exchange is considered a major hindrance to population divergence and, ultimately, to the evolution of new species. Where a geographic barrier to reproductive isolation is lacking, a biological mechanism for speciation is required to counterbalance the homogenizing effect of gene flow. Speciation with initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
209
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(213 citation statements)
references
References 38 publications
3
209
0
1
Order By: Relevance
“…Metrosideros operculata is a rupicolous shrub endemic to New Caledonia (Dawson, 1992) and is nested within a local radiation of the subgenus Mearnsia (Wright et al, 2000). Metrosideros sclerocarpa (Dawson in Green, 1990) is a species endemic to Lord Howe island that likely evolved in situ (Papadopulos et al, 2011) and is most commonly found near creeks. This species belongs to the subgenus Metrosideros, which also contains the Hawaiian species.…”
Section: Recent Emergence Of a Riparian Varietymentioning
confidence: 99%
“…Metrosideros operculata is a rupicolous shrub endemic to New Caledonia (Dawson, 1992) and is nested within a local radiation of the subgenus Mearnsia (Wright et al, 2000). Metrosideros sclerocarpa (Dawson in Green, 1990) is a species endemic to Lord Howe island that likely evolved in situ (Papadopulos et al, 2011) and is most commonly found near creeks. This species belongs to the subgenus Metrosideros, which also contains the Hawaiian species.…”
Section: Recent Emergence Of a Riparian Varietymentioning
confidence: 99%
“…Biogeographic work on birds and lizards has failed to turn up a single case of sister species on small islands (9, 10); similar conclusions come from a recent survey of several animal and plant groups (11). In response, Papadopulos et al (1) suggest that "speciation in the face of strong gene flow may be a botanical specialty. "…”
mentioning
confidence: 61%
“…By including genera in which molecular phylogenies involve a smaller percentage of the congeneric species (16-54%), Papadopulos et al (1) find nine more species that may have resulted from sympatric splits on LHI: two species in the genus Alyxia, two in Geniostoma, and two and three species, respectively, in the fern genera Grammitis and Asplenium. These cases, however, are more doubtful: incomplete phylogenies may miss some true sister species that live in other places, invalidating some examples of sympatric speciation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data from molecular markers and ecological studies show the potential for selection to drive divergence in the face of gene flow and recombination [37][38][39][40][41]. In his studies of Stephanomeria, Gottlieb was concerned with how initial divergence could have occurred and how the rarer derivative species could coexist with its progenitor at the same locality.…”
Section: Introductionmentioning
confidence: 99%